Inventory of Wetland Plants of Select Freshwater Environs of Kanyakumari District, with Emphasis on their Indigenous use - Deletta, G. Jerlin; Jeeva, S.; Mohan, V.; Parthipan, B. (Indian Forester, 2018)
Floristic studies were carried out for the period of two years (October 2014 and October 2016) in select ponds of Azhagapapuram village in Agastheeswaram taluk of Kanyakumari district, Tamil Nadu. A total of 65 angiosperm taxa belonging to 30 families, 53 genera, and 15 orders under 10 clades/groups were documented. The major clades were commelinids (23 species), lamiids (10 species) and monocots and asterids (7 species), Campanulids, Fabids and Malvids (5 species). Dominant families were Poaceae with 11 species followed by Cyperaceae (7), Fabaceae and Compositae (4 each), Convolvulaceae, Hydrocharitaceae and Amaranthaceae (3 each), Apocynaceae, Araceae, Commelinaceae, Nyctaginaceae, Onagraceae, Polygonaceae and Plantaginaceae were represented by 2 species each and the remaining 16 families by one taxon each. As regards morpho-ecologic characters, 32 taxa were found to be marshy and wetland plants, 16 emergent anchored hydrophytes, 7 floating anchored hydrophytes, 5 free floating hydrophytes and 5 submerged hydrophytes. Of the 65 taxa recorded 37 were found to have utility value. Most of the plants were recorded to have medicinal value, with 37 species being used in traditional system of medicine to treat over 55 ailments.